New spirobisnaphthalenes from an endolichenic fungus strain CGMCC 3.15192 and their anticancer effects through the P53–P21 pathway. Issue 67 (28th November 2019) - Li, Jingwen; Ding, Rong; Gao, Hao; Guo, Liangdong; Yao, Xinsheng; Zhang, Youwei; Tang, Jinshan
Abstract : New spirobisnaphthalenes from an endolichenic fungus strain and their anticancer effects mediated by the P53–P21 pathway. Abstract : Natural products from fungi have remained a rich resource for drug discovery. Here we report the isolation of three new spirobisnaphthalenes, namely sacrosomycin A-C (1–3 ), and three known analogues (4–6 ), from the ethyl acetate extract of a nonsporulating endolichenic fungus derived from Peltigera elisabethae var. mauritzii. The structures of these compounds were elucidated by IR, UV, MS, and NMR. Biological functions of these compounds were evaluated using cultured human cancer cell lines. Short-term cell growth and long-term cell survival assays show that compound 5 demonstrated the strongest cancer cell growth inhibition effect. We reveal that compound 5 induced both cell cycle arrest at the G2/M phase and cell death. Using western blotting, luciferase reporter assay and quantitative PCR (qPCR), we show that compound 5 induced up-regulation of the P53–P21 pathway, supporting the cell cycle arrest and growth inhibition effect of this compound. In contrast, these compounds did not induce cell death in a normal cell line. These results demonstrate a potential anticancer effect of this rare family of spirobisnaphthalene compounds isolated from endolichenic fungi.